The preventive and curative effects of melatonin against abdominal aortic aneurysm in rats - ARSAN, SİNAN; ÇETİNEL, ŞULE (MOSBY-ELSEVIER, 2018)
Objective: Oxygen free radicals are important components involved in the histopathologic tissue alterations observed during abdominal aortic aneurysms (AAAs). This study examined whether melatonin has protective or therapeutic effects against AAAs. Methods: Sprague-Dawley rats were divided into four groups. A CaCl2 model was used to induce AAA. Starting on the operation day (Mel+AAA+Mel group) or 4 weeks after the operation (AAA+Mel group), the rats received intraperitoneal melatonin (10 mg/kg/day) for 6 and 2 weeks, respectively. The control and AAA groups received vehicle for 2 weeks after the sham operation and AAA induction, respectively. Angiographic measurements were recorded at the beginning, week 4, and week 6 of the study. After decapitation, aorta tissues were taken for the measurement of malondialdehyde, 8-hydroxy-2'-deoxyguanosine, glutathione levels, and myeloperoxidase and caspase-3 activity. Matrix metalloproteinase (MMP)-2, MMP-9, tumor necrosis factor-a, and inducible nitric oxide synthase protein expressions were analyzed by Western blot technique. Aortic tissues were also examined by light microscopy. Results: CaCl2 caused an inflammatory response and oxidative damage indicated by rises in malondialdehyde and 8-hydroxy-2'-deoxyguanosine levels. Myeloperoxidase and caspase-3 activities were increased, but glutathione levels were reduced. On the one hand, MMP-2, MMP-9, tumor necrosis factor-a, and inducible nitric oxide synthase protein expressions were increased in the vehicle-treated AAA group. On the other hand, melatonin treatment reversed all of these biochemical indices and histopathologic alterations. Conclusions: According to the data, although melatonin tended to reverse the biochemical parameters given on week 4, the preventive effect is more pronounced when given concomitantly with AAA induction because values were closer to the control levels.
Keywords: OXIDATIVE STRESS; MATRIX METALLOPROTEINASES; MODEL; HYPERTENSION; INFLAMMATION; ANTIOXIDANT; ACTIVATION; EXPRESSION; MYELOPEROXIDASE; PROTECTS